Accidental and Late Diagnosis of Type A Aortic Dissection: Mimicking Unstable Angina Pectoris. (October 2022) - Alirezaei, Toktam; Irilouzadian, Rana; Khani, Mohammad
Aortic dissection is an infrequent diagnosis that usually presents with acute onset of sharp and severe tearing pain. It rarely presents with atypical symptoms, accompanied by a higher mortality risk that arises the delay in diagnosis. In this report, we discuss a type A aortic dissection case with a presentation of heaviness-like chest pain with no evidence of aortic dissection in his first echocardiography. The patient was treated for acute coronary syndrome (ACS), but on the follow-up, echocardiography aortic dissection was diagnosed accidentally. Differentiation between ACS and aortic dissection is critical in patient management. Each one has an entirely different treatment approach, and misdiagnosis can lead to catastrophic outcomes.